2019
DOI: 10.5539/ies.v12n10p75
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Self Efficacy-Sufficiency Levels of Individuals with Visual Impairment According to Some Variables

Abstract: This study was conducted with the aim of determining self efficacy-sufficiency levels of visually impaired individuals according to some variables. Bandura (1994) states that self-sufficiency, defined as an individual’s belief on operating a specific job, is an important factor for the athletes. Self-sufficiency results in choosing a field of study voluntarily, feeling a high motivation for accomplishing that job, endeavoring and spending time on the study. Self-sufficiency is about the individual’s specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…When the literature was examined, no study was found that examined the relationship between distance education perception and academic self-efficacy. However, it is seen that there are separate studies on the general / academic self-efficacy 2,[12][13][14][15][16] , and perception of distance education [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…When the literature was examined, no study was found that examined the relationship between distance education perception and academic self-efficacy. However, it is seen that there are separate studies on the general / academic self-efficacy 2,[12][13][14][15][16] , and perception of distance education [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…Visually impaired individuals are classified differently according to their visual level. The classification is also valid in sports branches (Dalbudak & Musa, 2019). IBSA has defined three classes at an international event for the athletes who are partially or completely blind.…”
Section: Yakup Akif Afyon 1*mentioning
confidence: 99%